Modulation of platelet activation and thrombus formation using a pan-PI3K inhibitor S14161. - Wenxiu Yi; Qiang Li; Jian Shen; Lijie Ren; Xiaohui Liu; Qi Wang; Sudan He; Qingyu Wu; Hu Hu; Xinliang Mao; Li Zhu (PLoS ONE, 2014)
The phosphatidylinositol 3-kinase (PI3K) signaling pathway is critical in modulating platelet functions. In the present study, we evaluated the effect of S14161, a recently identified pan-class I PI3K inhibitor, on platelet activation and thrombus formation. Results showed that S14161 inhibited human platelet aggregation induced by collagen, thrombin, U46619, and ADP in a dose-dependent manner. Flow cytometric studies showed that S14161 inhibited convulxin- or thrombin-induced P-selectin expression and fibrinogen binding of single platelet. S14161 also inhibited platelet spreading on fibrinogen and clot retraction, processes mediated by outside-in signaling. Using a microfluidic chamber we demonstrated that S14161 decreased platelet adhesion on collagen-coated surface by about 80%. Western blot showed that S14161 inhibited phosphorylation of Akt at both Ser473 and Thr308 sites, and GSK3β at Ser9 in response to collagen, thrombin, or U46619. Comparable studies showed that S14161 has a higher potential bioavailability than LY294002, a prototypical inhibitor of pan-class I PI3K. Finally, the effects of S14161 on thrombus formation in vivo were measured using a ferric chloride-induced carotid artery injury model in mice. The intraperitoneal injection of S14161 (2 mg/kg) to male C57BL/6 mice significantly extended the first occlusion time (5.05 ± 0.99 min, n = 9) compared to the vehicle controls (3.72 ± 0.95 min, n = 8) (P<0.05), but did not prolong the bleeding time (P>0.05). Taken together, our data showed that S14161 inhibits platelet activation and thrombus formation without significant bleeding tendency and toxicity, and considering its potential higher bioavailability, it may be developed as a novel therapeutic agent for the prevention of thrombotic disorders.